A geographic analysis of motor vehicle collisions with child pedestrians in Long Beach, California: comparing intersection and midblock incident locations. Issue 2 (1st June 2001) - Lightstone, A S; Dhillon, P K; Peek-Asa, C; Kraus, J F
Abstract : Objectives —The purpose of this study was to use geographic information system (GIS) software to locate areas of high risk for child pedestrian-motor vehicle collisions in the city of Long Beach and to compare risk factors between midblock and intersection collisions. Methods —Children 0–14 years of age involved in a motor vehicle versus pedestrian collision that occurred on public roadways in Long Beach, CA, between 1 January 1992 and 30 June 1995, were identified retrospectively from police reports. The GIS software program, ArcView, was used for spatial analysis and distance calculations. χ 2 Tests were used to compare the distribution of the characteristics between intersection and midblock collisions. Results —The average annual incident and fatality rate was 183.3/100 000 children/year and 2.4/100 000 children/year, respectively. Children less than 5 years of age were significantly more likely to be hit at a midblock location while those aged 5–9 and 10–14 were more often hit at an intersection. Intersection collisions were more likely to occur on major arterials and local streets, and the driver to be the primary party at fault (p<0.001). While intersection incidents tended to occur further from the child's home (64.4%) the majority of midblock incidents (61.5%) occurred within 0.1 miles of the child's residence. For both midblock and intersection locations, pedestrian collisions tended to occur more frequently in those census tracts with a larger number of families per census tract—a measure of household crowding and density. Conclusions —Future studies taking into consideration traffic volume and vehicle speed would be useful to focus prevention efforts such as environmental modifications, improving police enforcement, and educational efforts targeted at parents of younger children. As GIS illustrative spatial relationships continue to improve, relationships between pedestrian collision sites and other city landmarks can advance the study of pedestrian incidents.